IL-33 promotes ICAM-1 expression via NF-kB in murine mast cells - Takafumi Numata; Tomonobu Ito; Tatsuo Maeda; Chizu Egusa; Ryoji Tsuboi (Allergology International, 2016)
Background: IL-33, a member of the IL-1 cytokine family, binds to heterodimeric receptors ST2 and IL-1 receptor accessory protein, and activates Th2-type immune responses. The signals from the ST2 receptor are mediated by the two major pathways, including AP-1 and NF-κB molecules. The present study examined whether IL-33 induced ICAM-1 expression in bone marrow-derived mast cells (BMMCs). Methods: BMMCs from C57BL/6J mice, cultured in media containing IL-3 (20 ng/ml), were treated with IL-33 (50 ng/ml) for up to 72 h. ICAM-1 expression with mRNA and protein, degranulation of siRNA ICAM-1 transfected BMMCs, and cell adhesion were analyzed. In the in vivo part of the experiment rIL-33 (500 ng) was injected intradermally into the ear pinnae of mice and any resulting pathological changes were assessed. Results: ICAM-1 mRNA expression was increased one hour after IL-33 stimulation while ICAM-1 protein attained maximum expression levels 24 h after IL-33 stimulation. Moreover, IL-33-treated BMMCs showed increased cell adhesion to the LFA-1-coated plate. However, siRNA ICAM-1 transfected BMMCs did not affect Ag/IgE-mediated degranulation level compared to the wild control siRNA. Pre-treatment with a NF-κB inhibitor dramatically reduced ICAM-1 expression in IL-33-treated BMMCs, suggesting the involvement of NF-κB in the process. In vivo study, at 6 h after IL-33 treatment, MCs histologically showed up-regulated ICAM-1 expression though the number of tryptase-positive cells did not change. Conclusions: These data suggest that MCs increase ICAM-1 expression and activate LFA-1 positive cells in the early phase of skin inflammation in response to IL-33.